2017
DOI: 10.1016/j.gie.2016.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Role of per-oral pancreatoscopy in the evaluation of suspected pancreatic duct neoplasia: a 13-year U.S. single-center experience

Abstract: Background and Aims: The role of peroral pancreatoscopy (POP) in the evaluation of occult pancreatic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 18 publications
0
37
1
Order By: Relevance
“…In 97% of patients, technical success was achieved with successful advancing of the scope to the lesion, full visualization of the lesion, and proper diagnostic maneuvering. Adverse events were observed in 12% of cases, with most patients experiencing post-procedure abdominal pain and only 4% of patients developing post-procedure pancreatitis [27]. The authors concluded that pancreatoscopy can be highly successful and should be considered in patients with difficult pancreatic pathologies.…”
Section: Spyglass For Pancreatic Pathologiesmentioning
confidence: 94%
See 1 more Smart Citation
“…In 97% of patients, technical success was achieved with successful advancing of the scope to the lesion, full visualization of the lesion, and proper diagnostic maneuvering. Adverse events were observed in 12% of cases, with most patients experiencing post-procedure abdominal pain and only 4% of patients developing post-procedure pancreatitis [27]. The authors concluded that pancreatoscopy can be highly successful and should be considered in patients with difficult pancreatic pathologies.…”
Section: Spyglass For Pancreatic Pathologiesmentioning
confidence: 94%
“…Diagnostics 2020, 10, x FOR PEER REVIEW 6 of 11 patients experiencing post-procedure abdominal pain and only 4% of patients developing postprocedure pancreatitis [27]. The authors concluded that pancreatoscopy can be highly successful and should be considered in patients with difficult pancreatic pathologies.…”
Section: Spyglass For Pancreatic Pathologiesmentioning
confidence: 99%
“…They evaluated in a retrospective analysis a 13-year experience of patients who underwent pancreatoscopy to evaluate an indeterminate pancreatic duct stricture or suspected intraductal papillary mucinous neoplasms (IPMN). A final diagnosis of neoplasia was established in 42% (33/79) patients included in the study (adenocarcinoma in 12 cases and IPMN in 21) [48]. The authors reported an 87% accuracy in distinguishing malignant for benign lesions (sensitivity 87%, specificity 86%) [48].…”
Section: Diagnostic Applications Of Pancreatoscopy Pancreatic Stricturesmentioning
confidence: 97%
“…The most extensive experience reporting the use of pancreatoscopy for assessing pancreatic stenosis was recently reported by El Hajj et al [48]. They evaluated in a retrospective analysis a 13-year experience of patients who underwent pancreatoscopy to evaluate an indeterminate pancreatic duct stricture or suspected intraductal papillary mucinous neoplasms (IPMN).…”
Section: Diagnostic Applications Of Pancreatoscopy Pancreatic Stricturesmentioning
confidence: 99%
“…Peroral pancreatoscopy has been used sporadically for diagnosis of a number of pancreatic neoplasms, especially intraductal papillary mucinous neoplasm of the main pancreatic duct, besides ductal adenocarcinoma. The role of peroral pancreatoscopy in the evaluation of 79 patients with indeterminate pancreatic duct strictures, dilations, or with suspected or known main duct IPMN was published by El Hajj et al [126] in 2014. The technical success of POP was achieved in 97% of cases.…”
Section: Efficacy and Safety Of Cholangiopancreatoscopy (Cp)mentioning
confidence: 99%